2019
DOI: 10.1002/lary.27997
|View full text |Cite
|
Sign up to set email alerts
|

Congenital laryngomalacia: Is it an inflammatory disease? The role of vitamin D

Abstract: Objectives/Hypothesis Laryngomalacia is the most common cause of stridor in infants. The exact pathophysiology is still not well understood. Our objective was to investigate whether laryngomalacia is an inflammatory disease, focusing on the possible role of vitamin D. Study Design Case‐control study. Methods Sixty Egyptian infants and 60 mothers were included in this study. They were divided into four equal groups (n = 30 for each): infants with laryngomalacia (LM‐infants), control infants (C‐infants), mothers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
(60 reference statements)
1
8
0
Order By: Relevance
“…Children with laryngomalacia showed vitamin D deficiency and increased proinflammatory cytokine IL-6, which may result from dysregulation of the immune responses. Laryngomalacia could be an inflammatory disease secondary to maternal deficiency of 25(OH)-vitamin D with subsequent Vitamin D deficiency in exclusively breast-fed infants during neonatal and infantile periods [7].…”
Section: Etiologymentioning
confidence: 99%
“…Children with laryngomalacia showed vitamin D deficiency and increased proinflammatory cytokine IL-6, which may result from dysregulation of the immune responses. Laryngomalacia could be an inflammatory disease secondary to maternal deficiency of 25(OH)-vitamin D with subsequent Vitamin D deficiency in exclusively breast-fed infants during neonatal and infantile periods [7].…”
Section: Etiologymentioning
confidence: 99%
“…In laryngomalacia, the stridor often worsens with feeding, and the infant need to take breaks while feeding to breathe. 44 The stridor in the case of mild laryngomalacia usually improves with crying, as the tone of the pharynx is increased; conversely, in case of moderate to severe laryngomalacia, the stridor typically worsens with crying due to increased airflow through the severely collapsed larynx. In the case of infants with severe laryngomalacia, infants have been found to have shorter aryepiglottic folds in comparison with infants without laryngomalacia.…”
Section: Laryngomalaciamentioning
confidence: 99%
“…The severity of the respiratory problem increases while feeding, lying on the back, and crying. Generally symptoms start to be seen within the weeks after birth, and while there is clinical worsening around the fourth month, it is seen to spontaneously completely recover in the second year [ 7 , 8 ]. Diagnosis is based on the observation of supraglottic collapse in flexible laryngoscope examination [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The physiopathology of laryngomalacia has not yet been fully clarified. Theories have been proposed related to neurological pathologies caused by submucosal nerve hypertrophy or changes in the sensorimotor integrative function [ 8 ]. Recent studies have shown that vitamin D may have a role in the etiology of laryngomalacia [ 2 , 8 ].…”
Section: Introductionmentioning
confidence: 99%